Environmental sustainability and engineering performance of OPC-fly ash mortar mixs with different workability - Putri Zulaiha, Razi (2014)
Engineering performance and environmental sustainability of mortar mixes through the incorporation of different replacement levels of fly ash at 10%, 20%, 40% and 60% respectively were investigated. Samples of mortar were prepared by using four different water / binder ratios of 0.35, 0.40, 0.45 and 0.50, and were also prepared with different dosages of superplasticizer to give three ranges of workability that is normal, high and self-compacting spread flow. Engineering performance was assessed through compressive strength at 3, 7, 14, 28 and 90 days and the durability aspect through the water absorption test when mortar reached 28 days of age. Environmental performance or basically the sustainability aspect was assessed through the determination of CO2 footprint which denotes the environmental impact of each mix. The relationship that is to be investigated lies in the potential of CO 2 reduction in the mortar mixes, when cement was replaced by fly ash. Analysis of relative performance index for engineering performances and environmental sustainability found that regardless of the w/b ratios, for every type of flow, 60% replacement of fly ash gave the lowest relative performance index with an average of 50% less than OPC mortar. Cost analysis revealed that, cost per kg of mortar for self-compacting flow increased by 44% compared to normal flow. Optimum mix analysis found that with replacement of 10% to 20% of fly ash, gave a balance in environmental sustainability performance and engineering performance.